Case Report: Characterization of known (c.607G>C) and novel (c.416C>G) ELANE mutations in two Mexican families with congenital neutropenia - Núñez-Núñez, María Enriqueta; Lona-Reyes, Juan Carlos; López-Barragán, Brenda; Cruz-Osorio, Rosa Margarita; Gutiérrez-Zepeda, Bricia Melissa; Quintero-Ramos, Antonio; Becerra-Loaiza, Denisse Stephania (Frontiers in Immunology, 2023)
The most common causes of congenital neutropenia are mutations in the ELANE (Elastase, Neutrophil Expressed) gene (19p13.3), mostly in exon 5 and the distal portion of exon 4, which result in different clinical phenotypes of neutropenia. Here, we report two pathogenic mutations in ELANE, namely c.607G>C (p.Gly203Arg) and a novel variant c.416C>G (p.Pro139Arg), found in two Mexican families ascertained via patients with congenital neutropenia who responded positively to the G-CSF treatment. These findings highlight the usefulness of identifying variants in patients with inborn errors of immunity for early clinical management and the need to rule out mosaicism in non-carrier parents with more than one case in the family.